Individual exposure level following indoor and outdoor air pollution exposure in Dakar (Senegal). (May 2019) - Ndong Ba, A.; Verdin, A.; Cazier, F.; Garcon, G.; Thomas, J.; Cabral, M.; Dewaele, D.; Genevray, P.; Garat, A.; Allorge, D.; Diouf, A.; Loguidice, J.M.; et al.
Abstract: The consequences of indoor and outdoor air pollution on human health are of great concern nowadays. In this study, we firstly evaluated indoor and outdoor air pollution levels (CO, CO2, NO, NO2, PM10 ) at an urban site in Dakar city center and at a rural site. Then, the individual exposure levels to selected pollutants and the variations in the levels of biomarkers of exposure were investigated in different groups of persons (bus drivers, traders working along the main roads and housemaids). Benzene exposure levels were higher for housemaids than for bus drivers and traders. High indoor exposure to benzene is probably due to cooking habits (cooking with charcoal), local practices (burning of incense), the use of cleaning products or solvent products which are important emitters of this compound. These results are confirmed by the values of S-PMA, which were higher in housemaids group compared to the others. Urinary 1-HOP levels were significantly higher for urban site housemaids compared to semirural district ones. Moreover, urinary levels of DNA oxidative stress damage (8-OHdG) and inflammatory (interleukin-6 and -8) biomarkers were higher in urban subjects in comparison to rural ones. The air quality measurement campaign showed that the bus interior was more polluted with PM10, CO, CO2 and NO than the market and urban or rural households. However, the interior of households showed higher concentration of VOCs than outdoor sites confirming previous observations of higher indoor individual exposure level to specific classes of pollutants. Graphical abstract: Image 1 Highlights: Indoor organic volatile pollution higher than outdoor one. Highest urinary levels of oxidative stress and inflammatory biomarkers in urban subjects. Importance of indoor air pollution on the benzene metabolite S-PMA. Relevance of indoor habit to determine the exposure levels to selected VOCs. Correlation of biomarker of exposure with selected VOCs. Abstract : Outdoor and indoor air pollution analysis and human biomarker exposure evaluation.